Transforming Conflict into Collaboration: A Systematic Approach to Conflict Resolution at Antara East Java Indonesia News Agency - Hidayat, Rachmat; Kristiyono, Jokhanan (Technium Social Sciences Journal, 2025)
Conflict is an unavoidable part of organizational dynamics, necessitating systematic techniques for effective resolution. This study investigates the use of the Problem Solving and Decision Making (PSDM) paradigm to resolve conflicts at Antara East Java News Agency. During the first half of 2024, data were gathered using a qualitative case study approach, including in-depth interviews, participatory observations, and document analysis. The findings show that the PSDM model efficiently resolves organizational conflicts by rigorously diagnosing fundamental causes, encouraging inclusive decision-making, and implementing tailored remedies. Misaligned work allocations, imprecise communication routes, and conflicts between regional autonomy and centralized directives were among the most significant obstacles. Practical measures, such as the use of digital task management systems and collaborative decision forums, resulted in considerable improvements in operational efficiency and teamwork. This study advances conflict resolution theory by proving the PSDM model’s flexibility in media enterprises and integration with digital transformation challenges. It also offers tangible ideas for organizations dealing with comparable difficulties, highlighting the value of participatory and context-sensitive approaches. Future study should look at the model’s applicability in a variety of industries, cross-cultural contexts, and digital-first environments to increase its relevance and influence.